GREEN TECHNOLOGY POLICY AS A DRIVER FOR SUSTAINABILITY DEVELOPMENT: A CASE STUDY IN MALACCA - Ahmad, Nor Azilah Ahmad; Mohamed, Ahmad Fariz; Abdul Hamid, Nor Fazilah (Journal of Human Capital Development (JHCD), 2021)
ABSTRACT Melaka is known as the most historic state and is also a popular tourist destination in Malaysia. With the legacy of old buildings by past occupiers such as A Famosa, Christ Church, St. Paul’s Building and others recognize Melaka being one of the World Heritage States. Along time ago, the title of "Sleeping Hollow" state have been called for the slow economic situation and development conditions. Year 2000 to 2010 has shown a lot of environmental development and progress has been made, making Malacca eligible to be developed as a developed state in 2010. Next, Melaka continues to drive development opportunities to achieve green state urban status. The great expectation of the success of the mission is based on the needs of development in line with the will of the state government as well as the whole society. Researchers use qualitative methods where research on the documentation of official government materials as well as the search of information sources from journal articles, books and online data as the main reference. The findings have shown that the mission and strategy of development implementation are indispensable to continue to drive the state’s development for the sake of sustainability of the development itself. This study is also expected to contribute to clarifying the importance of green technology in driving the development of Melaka state now and beyond. Keywords: Green Technology, Policy Guideline and Future Development